Enhancements of Special Economic Zone Authority to Globalize its Companies Supply Chain - Abdallah Alalawin; Ahmad M. Qamar; Hesham Almomani; Mohannad Jreissat (International Journal of Supply Chain Management, 2020)
Companies around the world are getting more and more aware of the importance of implementing supply chain strategies, which happens to put companies into the map of the world. In order to respond effectively and efficiently to customer needs, companies have to select their supply chain strategies wisely.  One of the key supply chain strategies is the decision concerned with selecting sites and locations of facilities in which their operations are held. In many countries, Special Economic Zones (SEZs) were founded to host the operations of those facilities. SEZs have to attract companies by improving themselves to meet companies’ criteria. This study explores strategies that the Special Economic Zone Authority (ASEZA) implemented for the current companies to successfully sustain their position in the global market. Internal and external integration for these companies are the main focused criterion. A model to evaluate the opportunity for the internal and the external integrations in a specific SEZ is the main contribution of this paper, this model can be used by companies as one criterion of its criteria to select where it can locate its branches. As well, this model will promote ASEZA to attract new investors and companies to land their operations within its premises. Generally, the role of the SEZs to support the supply chain integration system. The model is tested on the Aqaba Special Economic Zone Authority (ASEZA), the opportunities to improve ASEZA capabilities to enhance the supply chain integration are identified as a result of implementing this model.